Challenges on Inclusive Tax Education in Indonesia: An Introduction - Leo B. Barus; Yudha Pramana (Journal of Entrepreneurship and Financial Technology, 2022)
The existence of Article 51 paragraph (2) letter c, paragraph (3), and paragraph (4) of Government Regulation Number 50 of 2022 indicates that the Directorate General of Taxes (DGT) (as the tax authority in charge of central taxes) and the Regional Government (as the regional/local tax authorities) must carry out an inclusive tax education program throughout the territory of the Republic of Indonesia. However, tax inclusion activities are not something that is easy. It is concluded that tackling the challenges of inclusive tax education in Indonesia can only be carried out if the vision is to serve all age ranges and levels of taxpayers in order to provide fair and participatory learning. Several solutions are teaching and learning processes, involving interactive media (such as games and videos), and involving technology (such as webinars, zoom, free or unpaid applications, and websites).